Programs of regional development revisited - case of the Russian Federation - Alexander Granberg; Alexander Pelyasov (European Regional Science Association (ERSA), 2005)
One of unexpected results of the economic reform in Russia was the rebirth of interest for regional programs and schemes as documents of strategic planning. Regional and municipal authorities, scientific community (not only Keynesian-like, but liberal economist Friedman-style as well), big and small business community, and civil society structures, now emerging in the Russian regions, all demonstrate their interest towards regional programs and schemes. Of course these documents are not of directive character now. They are of coordinative, partnership nature, oriented to consolidate efforts and resources of the state, business, citizens for modernization of the regional economy and increase of the GRP. Their ideology is based not only on principles of Soviet economists under the Gosplan era but on the achievements of institutional theory, theory of regional markets and the experience of regional policy in the European Union. However, in spite of new methodology of contemporary Russian regional programs and schemes, they neglect post-industrial challenges ahead of the country, in their concrete projects. For instance, cluster of federal programs of regional parity ("Diminishing discrepancies between Russian regions”, "Socio-economic development of Kaliningrad; the Kurils Islands; Far-Eastern regions; Southern republics in the European Russia”), in contrast with cluster of federal programs on the new economy, deals only with current social problems. These defects of contemporary federal and regional programs of socio-economic development can be seen precisely in the federal Program "Diminishing discrepancies between Russian regions intil 2015” approved by federal government in 2001. In this document possibilities to decrease striking contrasts between leaders and outsiders are connected with state financed projects of social and communal infrastructure in the 40 oblasts, republics and okrugs, whose level of social and economic development is beyond the average. Same problems in the EU regions are solved by projects directed to increase the quality of human resources. They are proved to be very efficient. During the last years Council for Research for Productive Forces (CRPF) has been eleborated four programs of socio-economic development: for Republic of Komi, Kemerovo and Jewish Oblasts, Khanty-Mansi autonomous Okrug. These documents are not comprehensive in contrast with their Soviet predecessors. They deal with numbered list of problems. They admit that regional development is multi-actors process. Structures of regional authorities, business, civil society participate in the projects under the Program. Many program measures are oriented to provide balance of interest for economic agents. Special attention is devoted to improve regional norms and rules of economic behaviour for economic actors in the new section titled "Development of the regional normative base”. CRPF is working under schemes of development and allocation of productive forces for Khanty-mansy autonomous Okrug and Chechen Republic. In comparison with programs schemes are more long-term documents of territorial planning. Also they include different variants of future development for every municipality. Experience of several federative states in the European Union meeting the challenge of striking inter-regional contrasts proves the necessity to elaborate new federal program "Innovative region” for the Russian Federation. It can be seen as analogue of the German program "Innoregio”. This new program should affirm new perception of creative region (now dominating perception in the federal programs is about region as the location of social problems), stimulate build-up of regional innovative systems, development of post-industrial activities. Russian programs and schemes as tools of regional policy which in the Soviet era were so distinct from Europeans by their directive ideology, central role of the state, slowly but straightforwardly are synchronizing with their analogues in the EU by their goals, tasks, and mechanisms.
Keywords: 330